EFISIENSI OPERASIONAL DAN KETERPADUAN PASAR DALAM TATANIAGA KARET RAKYAT DI PROVINSI JAMBI - Zainuddin Zainuddin (Universitas Batanghari Jambi, 2012)
As for the purpose of trading system in agricultural research activities are: (1) Identify the formation of channel trading system of smallholder rubber in Jambi province. (2) Knowing the achievement of operational efficiency in the trading system of smallholder rubber in Jambi province. (3) Analyze the market integration occurs in the trading system of smallholder rubber in Jambi province. Number of samples intermediary merchants at least 50 percent in each intermediate level ie village traders and wholesalers districts / counties. Quantitative analysis is used to assess the operational efficiency of rubber covering margin trading system trading system, the analysis section rubber prices received by farmers (farmer's share), the balance of benefit and cost analysis trading system institutions, and integration of the rubber market.Generally found three rubber trading system channels people are salauran I (farmers - rural traders - wholesalers - Crumb Rubber processing plant), channel II (farmers - traders village - processing plant), and channel III (farmers market - auction - factory Crumb Rubber processing). was oligopsoni with moderate to loose tightness levels. Operational efficiencies through the gum line auction market trading system in rural areas is higher than the traditional rubber trading system channels (intermediate traders rubber) based on differences in margin trading system, the prices received by farmers, and the balance of benefits and costs are taken institute rubber trading system. In the short term does not occur rubber market integration between farmers and the market rate or the rate of referral rubber processing plants, but in the long run market integration tends to be rubbery.Key word: Efficiency, Market, Rubber